The influencing of Inquiry-Based Learning on Science Conceptual Understanding in Terms of Primary School's Self-Efficacy - Mohamad Syarif Sumantri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of learning science in primary school is to provide students the chance to authentically develop their curiosity, to learn how to ask questions and look for explanations to natural occurrences based on evidence, and to think scientifically. The study's objective was to examine how the inquiry-based learning model and the direct learning model affected the self-efficacy of primary school students to understand science courses. This study is a quasi-experimental one with a 2x2 factorial design. In this inquiry, the first phase in the data analysis method was the normality and homogeneity tests. A two-way ANOVA analytic technique is then used to test data that is homogeneous and regularly distributed. The research was conducted at Pondok Benda Primary School in South Tangerang, Banten, was the site of the study. The sample was made up of 111 pupils in the fourth-grade primary school (aged between 10 and 11). Two-way variance data analysis method was followed by the Tukey test at a significance level of 0.05. should use the Lilliefors test to determine whether the data are normal, and the Bartlett results to determine whether the data are homogeneous.